Insights Into Cetacean Immunology: Do Ecological and Biological Factors Make the Difference? - Marsili, Letizia; Di Guardo, Giovanni; Mazzariol, Sandro; Casini, Silvia (Frontiers in Immunology, 2019)
The aim of this study was to evaluate the expression of Major histocompatibility complex (MHC) class I chain-related protein A (MICA) in fibroblast cell cultures of cetaceans (skin biopsies of free-ranging specimens and skin samples of freshly stranded cetaceans) by an immunofluorescence technique and to outline possible variations in MICA expression linked to different ecological and biological factors, while also investigating MICA expression after in vitro treatments with different contaminants. Free-ranging or stranded specimens of cetaceans were sampled in the Sea of Cortez (Mexico) (Balaenoptera edeni, Delphinus capensis and Orcinus orca) and in the Mediterranean Sea (Balaenoptera physalus, Physeter macrocephalus, Tursiops truncatus and Stenella coeruleoalba). Cell cultures were treated with an OC mixture, flame retardants, PAHs, MeHg and BPA. The 3 species from the Sea of Cortez showed higher basal activity of MICA and lower levels of DDTs and PCBs than the Mediterranean species. A Pearson's linear coefficient equal to -0.45 also confirmed this tendency to have high levels of MICA and low total OC levels. Treatment of cultured fibroblasts with different contaminants mostly resulted in the upregulation of MICA protein expression by at least one treatment dose; downregulation was also found in some species or treatments. MICA alteration indicates a state of stress of the organism and a modification of the immune system's response and can be proposed as a noninvasive immunological marker that can be measured in skin biopsy samples, thus offering a good alternative to blood measurements.